The Reality of Employing Web 2.0 Tools by Faculty Members in Technical Colleges in Education in Palestine (Palestine Technical College Journal for Research and Studies, 2019)
The study aimed to identifying the teaching members' actual recruitment of (Web 2) tools at the technical colleges in Palestine. To achieve the aims of the study; the descriptive analytical method was conducted, using a validated electronic questionnaire consisted of (31) items divided into two axes, in addition to an open question, was emailed to a sample consisted of (106) randomly chosen out of the teaching members at technical colleges in Gaza. Results of the study showed that the degree of the teaching members' recruitment of the (Web 2) tools at the technical colleges in Palestine was moderate. Whereas, the amount of problems that facing the teaching members at the Technical Colleges which prevent recruiting (Web 2) tools was a great degree. The results also showed that there were no statistically significant differences at (α < 0.05) between the average estimates on the fields ofstudy due to the following variables: (Technical Institution, Scientific Qualification, Experience). It was recommended to recruit the (Web 2) tools by the teaching members in education of the technical colleges, and educate academics and students on the importance of recruiting modern technologies as (Web 2) applications at technical colleges, its role in achieving effective learning and techniques for its development. It was also recommended adopting results of the study in solving problems facing the teaching members in recruiting (Web 2) tools and methods for problem treatment in education, adopting the electronic tests system for students, finding mechanism for teachers-students communication through the (Web 2) tools, recruiting it in the Palestinian curricula, and providing the appropriate environment for the application of this modernistic technique.
Keywords: (Web 2) Tools; Technical Colleges; Web 2; Teaching Members; Education in Palestine